Terrestrial organic carbon age and reactivity in the Yellow River fueling efficient preservation in marine sediments - Zhang, Yushuang; Galy, Valier; Yu, Meng; Zhang, Hailong; Zhao, Meixun (Earth and Planetary Science Letters, 2022)
The Yellow River is one of the largest suppliers of sediments and organic carbon (OC) to the ocean. Previous studies have revealed that OC transported by the Yellow River largely derives from the erosion of the Chinese Loess Plateau, which is dominated by pre-aged soil carbon and could be efficiently preserved in marine sediments. Here, we used ramped oxidation radiocarbon analysis (RPO-14C) to characterize the age and reactivity distribution of OC in two Yellow River suspended sediment samples and six Bohai Sea and Yellow Sea (BS–YS) surface sediments from a transect along the sediment transport pathway. RPO-14C independently characterizes the full spectrum of OC thermal stability and isotope compositions to reveal the source, age and reactivity structure of OC transported by the Yellow River and preserved in Chinese marginal sea sediments. We calculated the activation energy (E) distribution—a proxy for bonding environment and by extension reactivity—which, combined with 14C and stable carbon isotope (δ 13C) compositions, reveals OC origin and stability. Our data suggest that 96% of OC in Yellow River suspended sediments is biospheric and weathered petrogenic, while unweathered petrogenic OC only accounts for 4% which is almost an order of magnitude lower than the fossil OC estimates (32%) based on compound specific 14C analysis. RPO data reveal the prevalence of aged biospheric loess OC in the Yellow River. We use δ 13C, 14C and RPO-derived activation energy data to quantify the contribution of terrestrial OC to surface sediments in the BS–YS. The resulting estimates of terrestrial OC proto-burial efficiencies yield an average value of 89 ± 30%, revealing overall very high terrestrial OC preservation in the BS–YS. Additionally, and somewhat counter intuitively, we find that the preservation of terrestrial OC decreases with increasing E. This pattern may arise from an enhanced preservation of a pre-aged C4 plants derived fraction of the loess-derived OC associated with secondary clays characterized by smaller grain size and higher surface area. Alternatively, the high E component of the Yellow River OC might comprise partially weathered petrogenic carbon, undergoing further mineralization during transport from rivers to marginal sea sediments via marine organic matter priming.